Two new species of Homidia (Collembola: Entomobryidae) from Eastern China - Pan, Zhi-Xiang; Ma, Yi-Tong (Zootaxa, 2021)
Two new species of Homidia are described from Eastern China: H. hangzhouensis sp. nov. and H. wanensis sp. nov. The former is characterised by smooth chaetae e and l1 on labial base, two irregular transverse stripes on Abd. IV, absence of blue pigment on Ant. I−II and Abd. I−II and presence on Ant. III−IV, 7−9 macrochaetae on Abd. IV posteriorly and 24−34 smooth inner spines on dens. The latter can be identified by reduced blue body pigment, smooth chaeta e on labial base and having some posterior labial chaetae modified, appearing leaflike, 8−9 macrochaetae on Abd. IV posteriorly and 83 smooth inner spines on dens.